2012
DOI: 10.1159/000342007
|View full text |Cite
|
Sign up to set email alerts
|

Management of Stage IV Macular Holes: When Standard Surgery Fails

Abstract: Purpose: To report the surgical outcomes of reoperation of unclosed macular holes after initial vitrectomy with internal limiting membrane peeling. Procedures: Seven eyes of 7 patients were submitted to a second procedure in which five radial retinal incisions were made, as deep as the retinal pigment epithelium, beginning one hole diameter away from its borders and extending centripetally until the hole’s margins, avoiding the papilomacular bundle. Gas tamponade was performed and face-down positioning was rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 52 publications
0
32
0
Order By: Relevance
“…Reis et al reported a technique for addressing refractory macular holes in adults that involved making five radial retinal incisions with a 25-G needle or 25-G microvitreoretinal blade along the margin of the hole-a maneuver that, they postulated, relaxed the hole margin and allowed subsequent gliosis to close the hole. 24 Anatomical closure was achieved in seven of seven cases reviewed. 24 Similar techniques using full-thickness macular incisions have been described by both Smiddy 26 and Charles 27 to address refractory macular holes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Reis et al reported a technique for addressing refractory macular holes in adults that involved making five radial retinal incisions with a 25-G needle or 25-G microvitreoretinal blade along the margin of the hole-a maneuver that, they postulated, relaxed the hole margin and allowed subsequent gliosis to close the hole. 24 Anatomical closure was achieved in seven of seven cases reviewed. 24 Similar techniques using full-thickness macular incisions have been described by both Smiddy 26 and Charles 27 to address refractory macular holes.…”
Section: Discussionmentioning
confidence: 99%
“…24 Anatomical closure was achieved in seven of seven cases reviewed. 24 Similar techniques using full-thickness macular incisions have been described by both Smiddy 26 and Charles 27 to address refractory macular holes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Reiss et al described performing five radial incisions centered on the MH, extending one hole diameter away from the MH border, followed by gas tamponade in seven patients with refractory MHs. 26 They reported 100% anatomic success rate with a mean gain of 5.6 lines of vision. 26…”
Section: Increasing Retinal Tissue Compliancementioning
confidence: 98%
“…Likewise, there have been reports about arcuate retinotomies and relaxing radial retinal incisions aimed to move tissue to close refractory holes, although obviously these involve retinal incisions and associated risks. 12,13 We advocate use of a cohesive sodium hyaluronate ophthalmic viscosurgical device (OVD, Healon, Abbott Medical Optics Inc) to not only lyse retina-RPE adhesions but also maintain the potential subretinal space, stretching the adjacent retinal tissue until the conclusion of the air-fluid exchange.…”
Section: Introductionmentioning
confidence: 99%